The Influence of Ecologised Fertiliser Systems on the Elements of Fertility and Productivity of Winter Wheat - Anhelina Dubytska; Oksana Kachmar*; Oleksandr Dubytskyi; Oksana Vavrynovych (Наукові горизонти, 2022)
One of the strategic areas for the development of modern agriculture is the use of ecologised fertiliser systems composed based on the straw of agricultural crops with the addition of microbiological, humus or chelated fertilisers. This will allow restoring natural resources and getting environmentally friendly products. The purpose of the research was to study the effect of ecologised fertiliser systems on the physical and chemical processes and nitrogen regime of grey forest soil, the development of bio-productivity of winter wheat, and the content of basic microelements in grain. The following methods were used in the research: field, laboratory-analytical, mathematical-statistical. Application of N30P45K45 against the background of pea straw with the addition of a biostimulator and humus fertiliser mostly demonstrated modern approaches to technologies for managing the fertility of grey forest soils based on the principles of environmental safety and resource conservation. Such a fertiliser system provided alkalinisation of the soil solution, optimisation of the Ca2+ and Mg2+ content, improvement of the soil nitrogen regime. Under such conditions, optimal parameters of the production process elements (the number and mass of grains in the head) were formed. The most effective in the processes of accumulation of microelements was the organo-mineral system of the following composition: pea straw + N30R45K45 + chelated fertiliser. No excess of the maximum permissible concentration for Cu, Zn, Mn, or Fe was detected. Thus, to harmonise the ecological and productive functions of grey forest soil in the winter wheat cultivation system, a combination of alternative agriculture, which consists in reducing the use of mineral fertilisers, and partial biologisation, is considered promising. This is a way to optimise soil fertility and bio-productivity